The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1021/acsami.9b04926
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Ca Electrodeposition and Speciation Processes in Nonaqueous Electrolytes for Next-Generation Ca-Ion Batteries

Abstract: Electrochemical and analytical techniques were utilized to study Ca electrodeposition in nonaqueous electrolytes. Linear sweep voltammograms obtained at Au and Pt ultramicroelectrodes (UMEs) exhibit an inverse dependence between current density and scan rate, indicative of the presence of a chemical reaction step in a chemical–electrochemical (CE) deposition process. However, the magnitude of change in current density as a function of scan rate is larger at the Au UME than at the Pt UME. COMSOL simulation reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
109
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(118 citation statements)
references
References 45 publications
7
109
0
2
Order By: Relevance
“…Thus, the authors concluded that Ca 2+ is predominantly solvated by THF via the ethereal oxygen and is weakly coordinated, if at all, to BH4 -. [63] Overall, the findings point towards a surface-chemical role of the anion. Interestingly, the conductivities of Ca(BH4)2/THF electrolytes were significantly lower than their carbonate-based counterparts (Fig.…”
Section: Ca(bh4)2 In Thf With Au or Pt Electrodesmentioning
confidence: 90%
See 1 more Smart Citation
“…Thus, the authors concluded that Ca 2+ is predominantly solvated by THF via the ethereal oxygen and is weakly coordinated, if at all, to BH4 -. [63] Overall, the findings point towards a surface-chemical role of the anion. Interestingly, the conductivities of Ca(BH4)2/THF electrolytes were significantly lower than their carbonate-based counterparts (Fig.…”
Section: Ca(bh4)2 In Thf With Au or Pt Electrodesmentioning
confidence: 90%
“…Recently, Ta et al proposed an explanation for the functional role of BH4in the successful Ca(BH 4 ) 2 /THF system. [63] Linear sweep voltammetry with ultramicroelectrodes was performed on both Au and Pt working electrodes. The authors found that Ca deposition occurs through a chemicalelectrochemical mechanism, in which chemical H abstraction from BH4in the bulk electrolyte (and not THF) and surface H adsorption precedes subsequent reduction of Ca 2+ .…”
Section: Ca(bh4)2 In Thf With Au or Pt Electrodesmentioning
confidence: 99%
“…And for the first time, a Ca(BH 4 ) 2 electrolyte in THF was demonstrated for reversible calcium deposition and stripping at room temperature with low polarization (<0.1 V) and high coulombic efficiencies (≈95 %) by Bruce and Wang et al . and further confirmed by Gewirth et al . However, the reductive nature and insufficient anodic stability (ca.…”
Section: Methodsmentioning
confidence: 99%
“…Except for the self-characters such as electropositivity, ionic radius, and charges etc., it's generally accepted that metal plating/stripping potentials are dependent on the solvation/desolvation properties, which are highly in uenced by the ion concentration, type of solvents, substrates, and temperatures. [7][8][31][32] In the case of Ca-metal, the situations seem more complicated due to anion corrosion and large internal resistance resulted from the extremely insulative passivation layers. [4][5]7 Anyway, we found that the polarization potentials for Ca deposition/dissolution could be largely lowered through the increase of Ca 2+ concentration by adding Ca(BF 4 ) 2 .…”
Section: Voltage Tailorable Cwpdgc Ca-metal Batteriesmentioning
confidence: 99%